(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Ectopic pregnancy frequently occurs among women of reproductive age. Objective: The objective of the present study was to determine the incidence and socio-demographic characteristics of patients with ectopic pregnancy. Methodology: This cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, Bangladesh Medical College Hospital, Dhaka, Bangladesh, from January 2009 to December 2009, covering a period of one year. All clinically suspected cases of ectopic pregnancy among women of reproductive age admitted to the department were included. A detailed history was obtained, with particular attention to menstrual, obstetric, and contraceptive histories, followed by a thorough physical examination. The diagnosis of ectopic pregnancy was confirmed through relevant laboratory investigations and imaging studies. Results: The incidence of ectopic pregnancy at Bangladesh Medical College Hospital was 2.16%. The mean age of the study population was 24.0 ± 2.87 years. Ectopic pregnancy showed a strong association with higher parity, with para 2 being the most common (20 cases, 44.0%). The predominant risk factors included pelvic infection (33%), previous history of abortion or menstrual regulation (28%), and infertility (25%). A history of tuberculosis was reported in only 3.0% of cases. Conclusion: In conclusion, young women of parity two with a history of pelvic infection, abortion, or menstrual regulation were found to be most commonly affected by ectopic pregnancy. Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1): 75-80